Hashimoto's encephalopathy: Report of three cases - Jan-Shun Chang; Tien-Chun Chang (Journal of the Formosan Medical Association, 2014)
Both severe thyrotoxicosis and hypothyroidism may affect brain function and cause a change in consciousness, as seen with a thyroid storm or myxedema coma. However, encephalopathy may also develop in patients with autoimmune thyroid diseases independent of actual thyroid function level, and this is known as Hashimoto's encephalopathy. Although most patients are found to have Hashimoto's thyroiditis, less frequently they have Graves' disease. Clinical manifestations include epilepsy, disturbance of consciousness, cognitive impairment, memory loss, myoclonus, hallucinations, stroke-like episodes, tremor, involuntary movements, language impairment, and gait impairment. Hashimoto's encephalopathy is a relatively rare disease. As a good response can be obtained with corticosteroid therapy, early diagnosis and treatment is very beneficial for patients. Here we report three patients with Hashimoto's encephalopathy with typical manifestations of hallucinations that were associated with hypothyroidism, hyperthyroidism, and euthyroid status, respectively. They all showed a dramatic response to methylprednisolone pulse therapy.